2017
DOI: 10.1088/1741-2552/aa7590
|View full text |Cite
|
Sign up to set email alerts
|

Real-time inference of word relevance from electroencephalogram and eye gaze

Abstract: It was demonstrated that the interest of a reader can be inferred online from EEG and eye tracking signals, which can potentially be used in novel types of adaptive software, which enrich the interaction by adding implicit information about the interest of the user to the explicit interaction. The study is characterised by the following novelties. Interpretation with respect to the word meaning was necessary in contrast to the usual practice in brain-computer interfacing where stimulus recognition is sufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 44 publications
3
22
0
Order By: Relevance
“…This application of inferring information about the active mental context of the user was the third application we discussed. On one hand there is evidence that this approach can be used successfully to determine which of a small number of categories a subject aims to select ('has on mind') [16]. By using fixation-related potentials, stimuli can be presented to a user at a fast speed, as the inter-stimulus interval is determined by the subject, through their gaze.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This application of inferring information about the active mental context of the user was the third application we discussed. On one hand there is evidence that this approach can be used successfully to determine which of a small number of categories a subject aims to select ('has on mind') [16]. By using fixation-related potentials, stimuli can be presented to a user at a fast speed, as the inter-stimulus interval is determined by the subject, through their gaze.…”
Section: Discussionmentioning
confidence: 99%
“…), but a more straightforward application may be to determine appropriate reading levels in children. A study by [94] investigated the N400 in ages between 5 and 26 and found N400 amplitudes to be larger for younger subjects, with amplitudes stabilising around age [15][16]. A comprehension detection application may thus prove especially sensitive when aimed at children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These features are then used for statistical inferences, classification, and prediction. For instance, some variants of aggregated fixation-count and fixation-duration were used in studies reported in [14,15,19,21,39,41,59,63]. Eye-dwell time and/or visit time was used by Fahey et al [14].…”
Section: Related Work 21 Information Relevance and Eye-trackingmentioning
confidence: 99%
“…They reported an accuracy of 70%, but did not mention the specific eye-tracking features used. Wenzel et al [59] inferred the relevance of individual words from fixation duration and EEG features. They reported that only using fixation-duration gave an AUC of 0.51 (marginally better than chance), whereas combining fixation-durations with EEG features improved the AUC to 0.63.…”
Section: Comparison With Related Workmentioning
confidence: 99%